STRENGTHENING ONLINE TEACHER LEARNING COMMUNITIES TO BUILD A LIFELONG LEARNING SOCIETY - Wawan Krismanto (Novateur Publications, 2022)
Online learning communities are one of the contemporary issues that have been studied by many researchers in the field of education, including the setting of teacher communities. The emergence of various online learning communities among teachers is one of the positive impacts of the development of information and communication technology today. This technology makes iteasier for each individual to build a community and then carry out various activities in it. Through online learning communities, they allow them to share information, knowledge, and practical experiences and even various practical learning problems. Collaboration to create learning activities is also open and possible to be realized in online teacher-learning communities
Keywords: Online learning; online learning communities; lifelong learning society